Impact of structural modifications of IgG antibodies on effector functions - Damelang, Timon; Brinkhaus, Maximilian; van Osch, Thijs L. J.; Schuurman, Janine; Labrijn, Aran F.; Rispens, Theo; Vidarsson, Gestur (Frontiers in Immunology, 2024)
Immunoglobulin G (IgG) antibodies are a critical component of the adaptive immune system, binding to and neutralizing pathogens and other foreign substances.Recent advances in molecular antibody biology and structural protein engineering enabled the modification of IgG antibodies to enhance their therapeutic potential. This review summarizes recent progress in both natural and engineered structural modifications of IgG antibodies, including allotypic variation, glycosylation, Fc engineering, and Fc gamma receptor binding optimization. We discuss the functional consequences of these modifications to highlight their potential for therapeutical applications.